Transverse strength of railway tracks: part 2. Test system for ballast resistance in line measurement - Antonio De Iorio; Marzio Grasso; Francesco Penta; Giovanni Pio Pucillo; Vincenzo Rosiello (Fracture and Structural Integrity)
In the present paper, testing methods currently adopted to measure the in service ballast resistance are synthetically reviewed to identify the main sources of uncertainty influencing the test loads and to define an experimental methodology allowing the optimal control of the testing parameters without the introduction of spurious or parasitic actions on the track sample. An alternative testing system, which allows applying on a fullscale sample of a railway track testing loads very close the real ones, is presented. Of the new system, both the ways of use for measuring the transversal and axial ballast strength, the general procedure to carry out the experimentation and its application to a real scenario are described, highlighting its main advantages in terms both of modalities for applying the loads and of testing parameter control.